Cellular immunotherapy for refractory diffuse large B cell lymphoma in the chimeric antigen receptor-engineered T cell era: still a role for allogeneic transplantation? - Dreger, Peter; Fenske, Timothy S.; Montoto, Silvia; Pasquini, Marcelo C.; Sureda, Anna; Hamadani, Mehdi (Biology of blood and marrow transplantation, 2020)
Chimeric antigen receptor-engineered T (CART) cells are a promising new treatment option for patients with multiply relapsed and refractory (R/R) diffuse large B cell lymphoma (DLBCL). Because of the favorable outcome data reported for CART cells, uncertainty is emerging if there is still a role for allogeneic hematopoietic cell transplantation (allo-HCT) in the treatment of R/R DLBCL. This article provides an overview of available evidence and theoretical considerations to put these 2 types of cellular immunotherapy (CI) into perspective. Altogether, current data suggest that CART cells are preferred now over transplantation as first-choice CI in many clinical situations. However, the majority of patients will fail CART therapy, resulting in an unmet medical need where allo-HCT could be beneficial. In contrast, employing allo-HCT instead of CART cells as first CI should be presently restricted to situations where CART cell therapy is deemed not feasible or useful, such as patients with refractory cytopenia or incipient myelodysplastic syndrome. However, allo-HCT remains a standard treatment option as first CI for patients with chemosensitive R/R DLBCL when CARTs are not available or transplantation is preferred by the patient. Continuous collection and analysis of CI outcome data by professional registries appear to be of key importance for developing rational strategies of CI allocation and sequencing.
Gesehen am 15.06.2020